Rosvita de Gandersheim: Theater and Education in the 10th Century (Research, Society and Development, 2022)
The present article is meant to think the medieval theatre through the writings of Hrotsvitha of Gandersheim (935-1002). At this research we have studied her educational work, while she lived in a monastery in nowadays Germany. Due to its historiographical nature, this is a bibliographic and documental research in which we analyse this character’s path through her works: Dramas and Obra dramática. We also work with authors as Lauand (1986) and Bovolim (2005). We consider this nun an intellectual with great relevance to education’s history because we have eight poems, six theatre pieces and two epics from her, all of them being religious and pedagogic. The nun was an expressive figure for medieval theatre’s history, for she taught, by those means, important concepts of mathematics, also, she dramatized primitive Christian moral and ethical values, that needed to be recovered. So, by social history’s precepts, with a special attention to the concept of long duration, we analyse Hrotsvitha of Gandersheim’s work as an intellectual from/for the history of medieval education.